Kontinuitas Pendidikan Seni Teater di Komunitas Celah-Celah Langit Bandung - Muhammad Sirojul Muniir; Yudi Sukmayadi; Juju Masunah (Universitas Pendidikan Mandalika, 2023)
This research aims to describe the process of actor education, which includes materials, methods, and indicators of learning outcomes in the Celah-Celah Langit community as an effort to continuity theater arts education in Bandung. This research method used a descriptive method with a qualitative approach, where the data collection techniques include observation, interviews, and documentation. The data analysis technique of this research used interpretative analysis. The results of this study indicated that art education in the community had a curriculum structure designed based on the community owner, namely (1) Actorial learning material obtained from the historical experience of the Community founder, (2) lecture learning methods used in teaching, with a game model for learning material (3) indicators of learning achievement as an actor who lives the character and increases maturity.